LANDING OF SMALL AND MEDIUM-SIZED BUSINESS V CURRENT ECONOMICS TSONDITIONS - LOPATOVSKA, Oksana; MELNYK, Alyona (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Financing small and medium-sized businesses in Ukraine is a relevant and significant topic, as these enterprises are key players in the economy, contributing significantly to the country’s gross domestic product and job creation. However, small and medium-sized businesses often face various problems, including a lack of internal funds for sufficient financing of their operations. Typically, the main source of financial resources for business development in such cases is financing through loans. The purpose of this article is to identify the various problems and opportunities for financing small and medium-sized businesses. It is worth noting that the government of Ukraine pays special attention to supporting small and medium-sized enterprises (hereinafter referred to as SMEs), which helps promote the development of this sector. For example, establishing a simplified tax system, creating credit programs for small and medium-sized enterprises, supporting young entrepreneurs, and improving access to credit for this sector.